Heritage Branding and The Value of Nostalgia: The Case of Kopi Toko Djawa in Bandung - Benedikta, Clara; Ekomadyo, Agus S.; Viana, Anita (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Coffee is embedded in everyday life as a tradition or ritual within individuals or social communities. Coffee shapes social interactions and cultural practices. Kopi Toko Djawa Pasar Cihapit evokes memories through its spatial dimension. The existence of Kopi Toko Djawa Cihapit gives a nostalgic impression because of its location. Apart from that, the impression of nostalgia from an architectural perspective is also reflected in the interior, which presents a “heritage” atmosphere and strengthens the visitor’s experience in interpreting heritage values in the spatial dimension. The contribution that will be conveyed through this article is a deeper understanding of nostalgia in the form of memory and architecture through coffee in traditional markets, as well as highlighting how this influences community to its dynamics and local identity. This article explores nostalgia in memory and architecture through coffee in conventional markets. The article examines coffee’s cultural and historical significance, using ethnographic methods and interviews to reveal the coffee heritage at Kopi Toko Djawa Cihapit. This research enriches understanding of cultural nuances and underscores the importance of preserving coffee heritage in an architectural context. Qualitative data from the literature, field observations, and interviews with the first barista at Kopi Toko Djawa Cihapit underlie this research.